2019
DOI: 10.3390/ijms20051202
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Levels of Preβ1-HDL Are Significantly Elevated in Non-Dialyzed Patients with Advanced Stages of Chronic Kidney Disease

Abstract: In chronic kidney disease (CKD), the level of high-density lipoprotein (HDL) decreases markedly, but there is no strong inverse relationship between HDL-cholesterol (HDL-C) and cardiovascular diseases. This indicates that not only the HDL-C level, but also the other quantitative changes in the HDL particles can influence the protective functionality of these particles, and can play a key role in the increase of cardiovascular risk in CKD patients. The aim of the present study was the evaluation of the paramete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
16
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 42 publications
3
16
0
1
Order By: Relevance
“…In particular, we found that HDL distribution was shifted toward smaller HDL 3 particles in both patient groups, because of impaired HDL maturation, due to reduced apoA‐I level and LCAT activity. Our findings were further extended in a recent study in nondialysis CRD patients by Kuchta and colleagues . They found that the level of preβ1‐HDL, the smallest HDL particles in plasma, increased in advanced stages of CRD .…”
Section: Hdl Characteristics and Pon1 Activity—a Bridge Toward Hdl Fusupporting
confidence: 85%
See 2 more Smart Citations
“…In particular, we found that HDL distribution was shifted toward smaller HDL 3 particles in both patient groups, because of impaired HDL maturation, due to reduced apoA‐I level and LCAT activity. Our findings were further extended in a recent study in nondialysis CRD patients by Kuchta and colleagues . They found that the level of preβ1‐HDL, the smallest HDL particles in plasma, increased in advanced stages of CRD .…”
Section: Hdl Characteristics and Pon1 Activity—a Bridge Toward Hdl Fusupporting
confidence: 85%
“…Our findings were further extended in a recent study in nondialysis CRD patients by Kuchta and colleagues . They found that the level of preβ1‐HDL, the smallest HDL particles in plasma, increased in advanced stages of CRD . Preβ1‐HDL particles are considered as initial acceptors of cholesterol in the first step of the RCT process .…”
Section: Hdl Characteristics and Pon1 Activity—a Bridge Toward Hdl Fusupporting
confidence: 83%
See 1 more Smart Citation
“…Elevated concentrations of preβ1-HDL have been also observed in patients with coronary artery disease, which suggests the relationship between higher levels of preβ1-HDL and the risk of CVD [126,127]. Kuchta et al [125] reported a substantial increase of preβ1-HDL in patients with 3a-4 stages of CKD, which was probably associated with a compromised LCAT-dependent conversion of preβ1-HDL into α-migrating HDL. Other studies have confirmed that CKD decreased both levels and activity of circulating LCAT, and in advanced stages of the disease, it downregulated hepatic LCAT gene expression [128,129].…”
Section: Cardiovascular Risk Related To Modifications Of Hdl Particlementioning
confidence: 99%
“…Therefore, low levels of large HDL particles and high levels of small HDL particles seem to protect against the incidence of cardiovascular events [16,124]. Kuchta et al [125] demonstrated that, in CKD patients with stages 3a-4, the concentration of preβ1-HDL was increased. Elevated concentrations of preβ1-HDL have been also observed in patients with coronary artery disease, which suggests the relationship between higher levels of preβ1-HDL and the risk of CVD [126,127].…”
Section: Cardiovascular Risk Related To Modifications Of Hdl Particlementioning
confidence: 99%